The effects of local pulsed magnetic field with intraosseous implant on clotting time and calcium level (Mustansiria Dental Journal, 2018)
Background: Many researches indicated that magnetic field had effect on clottingtime and serum calcium level when it was used for stimulation of bone healingand growth. This in vivo study was carried out to evaluate the effect of localpulsed magnetic on clotting time and serum calcium level when used forstimulation of intraosseous implant.Materials and Methods: Forty eight oryctologus cuniculus male rabbits were used inthis study, they divided into two controlled groups and two experimental groupsand each group consist of 12 animals, all experimental groups exposed to (50gauss) pulsed magnetic field strength. Clotting time and calcium level measured atintervals of time (2, 4, 6and 8) weeks of healing periods.Results: the result indicated that theirs no significant differences between thecontrolled group and other groups for (50 Gauss) pulsed magnetic field whichindicate no harmful effect of magnetic field on clotting time and calcium level.Conclusion: The use of (50 Gauss) pulsed magnetic field show no noticeable affecton serum calcium level and clotting time.